Development and Assessment of Shelf-Stable Spicy Snacks Prepared from Buffalo Tripe by Incorporating Sichuan Pepper (Timur) - Rayamajhi Sherpa, Dawa; Ghimire, Laxmi; Subba, Dilip; Gautam, Rishi Raj (Journal of Food Science and Technology Nepal, 2018)
A study was conducted for the preparation of the shelf stable spicy tripe snack from buffalo tripe with two different spices mixture. The main difference in the spice mixture is that one mix did not contain the Sichuan Pepper (timur) which is called as control batch and another contained it which is called as treated batch. Trial of product development was performed for three times where the combinations of the spices were altered till best combination was obtained. The prepared products were compared to sensory, microbiological and chemical analysis. The timur treated sample was found significantly superior in terms of taste and overall acceptability. The results of microbiological and physiochemical analysis showed that the timur-added snack more shelf-stable than un-added snack. Proximate composition of the best formulation moisture, crude protein, crude fat, crude fiber, total ash, salt and carbohydrates by difference are 43.915±1.5, 10.447±0.5, 15.203±0.5, 1.263±0.7, 2.7±0.7, 5.554±0.6 and 20.919±2.3, respectively.